الاحتياجات التدريبية لمهارات إدارة الصف لدى معلمي مرحلة التعليم الثانوي في مدينة بنغازي - الرفادي ميكائيل إدريس; الجراري خديجة محمد (Scientific Journal of University of Benghazi, 2021)
This study aims to determine the level of training needs in classroom management skills among high school teachers in the city of Benghazi, Libya, in the light of teachers' gender, major, and job experience. The population of the study consisted of (7574) high school teachers in (44) schools. A random sample of (400) teachers was selected. A questionnaire was used to collect data, consisting of (38) items. The face validity and the reliability of the Cronbach Alfa coefficient were both tested and found to be satisfying. The study findings are as follows: The high school teachers revealed training needs in classroom management skills related to students' classroom interaction. There are no significant differences among teachers in training needs due to their scientific major (arts/science). There are significant differences among teachers in training needs due to their gender (male/female) in the favour of male teachers. There are no significant differences among teachers in training needs due to their job experience.